Evaluation of the oxidative profile of critical patients hospitalized in adult intensive care unit - Brinati, Lídia Miranda; Januário, Carla de Fátima; Cardoso, Silvia Almeida; Moreira, Tiago Ricardo; Bastos, Daniel Silva Sena; Oliveira, Leandro Licursi de; Salgado, Patrícia de Oliveira (Ciência e Natura, 2021)
The objective of this work was to evaluate and correlate the oxidative stress in patients with uncontrolled blood glucose levels (hyperglycemia or hypoglycemia) hospitalized in an intensive care unit (ICU). This was a cross-sectional study, performed with 26 patients in an ICU of a hospital in the Zona da Mata in Minas Gerais. Patients with uncontrolled blood glucose levels were evaluated in two moments: on the day of admission (T0) and one day after the uncontrolled glycaemia (DG1). The evaluation of the oxidative profile was determined by the dosage of serum total antioxidant capacity, based on the ability of ferric reduction, determination of enzymatic activity of Superoxide Dismutase, Catalase and Glutathione S-Transferase, lipid peroxidation products and carbonylated proteins. The levels of ferric reducing ability decreased significantly, whereas the activity of the Superoxide Dismutase enzyme increased significantly after uncontrolled glycaemia in relation to the initial time. Although the lipid peroxidation did not change between the times evaluated, the damage marker significantly reduced, shown by carbonylation of proteins after the uncontrolled glycaemia. The critical patients evaluated in this study present altered oxidative profile after the uncontrolled glycaemia, a common problem that imposes the worst prognoses.